Formação continuada de professores de matemática de uma rede municipal de ensino : perspectivas para inovação na educação - Dall'Acua, Graziele (My University, 2025)
This PhD Thesis, under the Graduate Program in Education at the University of Caxias do Sul, within the Research Line "Educational Processes, Language, Technology, and Inclusion," investigates a continuing education program for Mathematics teachers working in the final years of elementary education in the Municipal School System of Flores da Cunha, RS, Brazil. The general objective was to analyze aspects of continuing education aimed at Mathematics teachers working with elementary school students, in order to develop pedagogical practices that enable innovation. The theoretical framework is based mainly on Paulo Freire (1996), António Nóvoa (2009, 2019, 2021, 2023), and Francisco Imbernón (2009), among other authors who support the proposed reflections. The research also draws on epistemological conceptions related to Mathematics teachers and everyday school life, based on the work of Fernando Becker (2012). A qualitative approach with an exploratory character was adopted, grounded in action research and a dialectical perspective. The research instruments included analysis of municipal educational documents and a continuing education program for Mathematics teachers, structured in two pedagogical components: a podcast and a study group. Data were produced through field diary records and analyzed using an approach inspired by the principles of Discursive Textual Analysis, following the assumptions of Moraes and Galiazzi (2007). The analysis of the empirical corpus led to the emergence of three categories: planning, Mathematics teacher, and innovation. The results indicate that the continuing education initiative contributed to critical reflection on pedagogical planning, promoting practices that support innovation and strengthen the professional identity of the participating teachers. The testimonies also reveal that continuing education, when aligned with the real teaching context and centered on teacher protagonism, has a significant impact on improving the quality of teaching and student learning in the final years of elementary education. Therefore, this dissertation argues that placing the teacher at the center of the formative process, through attentive listening and collaborative dialogue, constitutes an innovative action, enabling teachers to reflect on and reframe their practice alongside peers, fostering changes that enhance educational processes and promote innovation in education. Thus, the proposed continuing education for Mathematics teachers has proven to be a pedagogical innovation within the municipal education network of Flores da Cunha, standing out as a powerful formative experience with strong potential for becoming municipal public policy and being replicated and adapted to other educational contexts. [resumo fornecido pelo autor]
A presente tese, vinculada ao Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul, na Linha de Pesquisa "Processos Educacionais, Linguagem, Tecnologia e Inclusão", tem como objeto de estudo investigar formação continuada para professores de Matemática que atuam nos Anos Finais da Rede Municipal de Ensino de Flores da Cunha - RS. O objetivo geral foi analisar aspectos da formação continuada com professores de Matemática que atuam com estudantes do Ensino Fundamental da Rede Municipal de Ensino de Flores da Cunha - RS, de modo a constituir práticas pedagógicas que possibilitassem a inovação. O referencial teórico adotado fundamenta-se, principalmente, em Paulo Freire (1996), Antônio Nóvoa (2009, 2019, 2021, 2023) e Francisco Imbernón (2009), entre outros autores que subsidiam as reflexões propostas. A pesquisa também se apoia nas concepções epistemológicas que tratam do professor de Matemática e do cotidiano escolar, com base nos estudos de Fernando Becker (2012). O método adotado foi de abordagem qualitativa, com caráter exploratório, fundamentado na estratégia da pesquisa-ação e em uma perspectiva dialética. Os instrumentos de investigação incluíram análise de documentos educacionais do município e uma formação continuada para professores de Matemática, estruturada em dois momentos pedagógicos, constituídos por podcast e grupo de estudos. Os dados foram construídos por meio de registros em diário de campo e analisados com base em abordagem inspirada nos fundamentos da Análise Textual Discursiva, conforme os pressupostos de Moraes e Galiazzi (2007). Da análise do corpus empírico resultaram três categorias: planejamento, professor de Matemática e inovação. Os resultados indicam que a formação continuada contribuiu para a reflexão crítica sobre o planejamento pedagógico, promovendo práticas que possibilitem a inovação e o fortalecimento da identidade profissional dos professores protagonistas da pesquisa. Os depoimentos evidenciam, ainda, que a formação continuada, quando articulada ao contexto real de atuação e pautada no protagonismo do professor, tem influência na qualificação do ensino e no aprimoramento da aprendizagem dos estudantes dos Anos Finais do Ensino Fundamental. Portanto, esta tese defende que ao colocar o professor como centro do processo formativo, uma formação continuada sustentada na escuta atenta e no diálogo colaborativo, configura-se como uma ação inovadora, pois possibilita que o próprio professor pense, reflita e ressignifique sua prática junto a seus pares, promovendo mudanças que qualificam os processos educacionais e potencializam a inovação na educação. Sendo assim, a proposta de formação continuada direcionada aos professores de Matemática consolidou-se como uma inovação pedagógica no contexto da Rede Municipal de Ensino de Flores da Cunha, revelando-se uma experiência formativa potente, com forte potencial para se constituir em política pública municipal e possibilitar sua replicação e adaptação a outros contextos educacionais. [resumo fornecido pelo autor]
Keywords: Professores de Matemática; Professores - Formação; Ensino fundamental - Flores da Cunha (RS); Matemática (Ensino fundamental); Inovações educacionais; Mathematics teachers; Teachers, Training of; Elementary education - Flores da Cunha (Brazil); Mathematics (Elementary education); Educational innovations